ANALISIS PRAKTEK MANAJEMEN LABA DENGAN DISCRETIONARY ACCRUAL SEBELUM DAN SESUDAH PERUBAHAN TARIF PAJAK PENGHASILAN BADAN MENURUT PP NOMOR 30 TAHUN 2020 (STUDI KASUS PERSEROAN TERBUKA YANG LISTING DI BEI 2020) - Novea Beng Nuramanda (Jurnal Trial Balance, 2023)
This study aims to compare the level of discretionary accruals between before and after the decline in the domestic corporate income tax rate according to Government Regulation No. 30 of 2020. The sample of this study is the consumer goods sub-sector manufacturing listed on the Indonesia Stock Exchange and has published its financial statements from 2019-2020. The analytical method in this study uses descriptive analysis to determine the value of discretionary accruals by using a comparative technique used to compare the level of discretionary accruals between before and after the decline in corporate income tax rates according to PP 30 of 2020. The results showed that there was a decrease in operating profit in 2020 where the tax rate was lower than before the tariff reduction. This shows that in absolute terms, accruals in 2020 are lower, so there is no significant difference, this indicates that management does not use accruals for tax savings.